Modelling of high efficiency miniature aerocyclone - Aiman Hakim, Badarisman (2010)
Cyclone separation is one of the largely recognized methods of removing particulate in air, gas or water stream without help from filters. Cyclone is favourite separation device in various industries due to its simplicity, inexpensive design and minimum operational cost. In this research, the objective is maximizing the performance of miniature aerocyclone. The performance of aerocyclone can be analyzed by its collection efficiency and pressure drop. In past studies, expensive and time consuming experiment were conducted in order to analyze the performance of cyclone, butComputational Fluid Dynamics (CFD) software that being implemented in this researchhas successfully solve the problem. FLUENT is a commercially available CFD code that utilizes the finite volume formulation to carry out coupled or segregated calculations. Forthe turbulent flow in a cyclone the key to the success of CFD lies with the accurate description of the turbulent behavior of the flow. The simulation methodologies involve 5 steps before the simulation data can be verified with experimental data. The simulation starts with meshing of miniature cyclone via Gambit software. The meshed cyclone was then transferred into FLUENT software for simulation, where all the boundary condition is programmed in the software. After simulation completed, the data was then extracted and converted in the function of cyclone collection efficiency and pressure drop. The results show the influence of inlet velocity and exit tube size on cyclone performance and significant conclusion were made. The performances of turbulence model used in the simulation were then compared.